(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
Abstract: This paper introduces a novel methodology that utilises rapid prototyping and collaborative robotics to enhance spinal surgeries. The proposed approach enables the quick fabrication of customised laminar plates for vertebrae through Stereolithography (SLA) 3D printing, employing the biocompatible BioMed Photopolymer resin (USP Class IV). The methodology utilised involves converting Digital Imaging and Communications in Medicine (DICOM) format files or point cloud 3D data from 3D scanning into standard tessellation format (STL). This data is then utilized for reverse engineering and CAD modelling of the required laminar plate. The resulting plate is structurally unique and serves as a datum jig for the precise placement of posterior pedicle screws, ensuring accurate screw trajectory compared to the traditional free-hand technique. Acknowledgments The authors would like to acknowledge the contributions from Dr. Steven Battersby, Mark Golab, academic and technical teams within the Product Design Department and Engineering Department at Nottingham Trent University. The authors state no external funding involved. Author’s statement The authors state no conflict of interest. Informed consent has been obtained from all individuals included in this study.